"Aha!" is stronger when preceded by a "huh?": presentation of a solution affects ratings of aha experience conditional on accuracy. (3rd July 2019) - Webb, Margaret E.; Cropper, Simon J.; Little, Daniel R.
Abstract: Insight has been investigated under the assumption that participants solve insight problems with insight processes and/or experiences. A recent trend has involved presenting participants with the solution and analysing the resultant experience as if insight has taken place. We examined self-reports of the aha experience, a defining aspect of insight, before and after feedback, along with additional affective components of insight (e.g., pleasure, surprise, impasse). Classic insight problems, compound remote associates, and non-insight problems were randomly interleaved and presented to participants. Solution feedback increased ratings of aha experience in both insight and non-insight problems, with this result being driven by responses to solutions that were initially incorrectly generated. Ratings of aha for correctly generated solutions decreased after the correct solution was presented. These findings have implications for insight research paradigms as well as informing teaching methods.